Five-Year Licensure Examination Performance of Library and Information Science Graduates - Lascano, Elizabeth A.; Bansiong, Apler J. (Asian Journal of Contemporary Education, 2017)
Licensure examination performance of graduates is one measure of the effectiveness of curricular programs. This study analyzed the five-year performance of 159 BLIS graduates in the Librarians’ Licensure Examination in from 2011 to 2015. Findings reveal that the passing the graduates’ passing rates were statistically consistent in the five-year duration. The average passing rate was moderately high at 57.89%, but the mean general rating was only 73.23%. The general ratings had a slightly platykurtic, negatively skewed distribution. Overall, the institutional passing rate surpassed the national passing rate by 45.12%. Passing rates were highest in Information Technology, Indexing and Abstracting, and Library Organization and Management. Lower passing rates were posted in Selection and Acquisition of Library Materials, and in Cataloguing and Classification. The first timers, and the review center attendees, outperformed their respective counterparts, while the male and female examinees were statistically even. The first timers scored better than the repeaters in five areas, save cataloguing and classification. Meanwhile the male examinees and the center-reviewers were better than their counterparts on only one area - Library Organization and Management, and Selection and Acquisition of Library Materials, respectively. Recommendations as to the result of this study were proposed.